-6m-6=24

Simple and best practice solution for -6m-6=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6m-6=24 equation:


Simplifying
-6m + -6 = 24

Reorder the terms:
-6 + -6m = 24

Solving
-6 + -6m = 24

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -6m = 24 + 6

Combine like terms: -6 + 6 = 0
0 + -6m = 24 + 6
-6m = 24 + 6

Combine like terms: 24 + 6 = 30
-6m = 30

Divide each side by '-6'.
m = -5

Simplifying
m = -5

See similar equations:

| 3x^2-36x-10=o | | 5x-6z=-17 | | 13x+8y=123 | | y-2=.75x-6 | | 6x+5+7x-3=28 | | 15+4n=9n | | -8x-22=23-5x | | 19x+1=x+37 | | -3(2x-6)=12 | | A^2-12a-13=0 | | 9(3)-(-6)+7= | | 2x-12=2+x | | 64c^2=25 | | 2(7+x)=-36 | | b/5+1/3=17 | | 11x=16500 | | (7+x)=-36 | | 5(v-7)=-45 | | y-13=-.8x-(-5) | | 0.6666x+1=x-4 | | -6t+t^2=0 | | V=Vlw | | 4r=250 | | y+8=-4 | | 50x^2+25x=0 | | y+(-12)=24 | | 8/7+7m/5=96/35 | | 5d+9+2+3d= | | 1=5n-5-7n | | 3=3v+6 | | 90-k=12 | | 20x+5y=180 |

Equations solver categories